Analysis of Occupational Health and Safety Risks in the Palm Oil Processing Industry Using the HIRARC Method - Nurul Ilmi (Journal of Industrial System Engineering and Management, 2025)
The palm oil production industry is characterized by physically demanding tasks, high-temperature processes, and suboptimal working conditions, all of which contribute to a high risk of workplace accidents and health issues. At PT XX, 80% of reported work accidents are attributed to unsafe actions by workers, highlighting the need for a structured occupational health and safety management system. This study aims to identify hazards, assess occupational risks, and recommend appropriate control measures using the HIRARC (Hazard Identification, Risk Assessment, and Risk Control) method. Data were collected through field observations, interviews with 18 workers and 5 safety experts, and documentation across three key workstations: the loading ramp, sterilizer, and classification stations. The analysis identified a total of 15 work activities, with 3 classified as high-risk, 4 as medium-risk, and 8 as low-risk. High-risk activities were primarily related to exposure to high temperatures and confined workspaces. Control measures focused on engineering solutions, administrative controls, and the consistent use of Personal Protective Equipment (PPE). The application of the HIRARC method proved effective in systematically identifying and assessing risks, as well as in formulating targeted control strategies to reduce unsafe conditions and improve overall workplace safety performance. The study concludes that implementing the HIRARC framework significantly contributes to enhancing occupational health and safety in palm oil production environments.